Tissue Oxygen Saturation Mapping with Magnetic Resonance Imaging. Issue 9 (September 2014) - Christen, Thomas; Bouzat, Pierre; Pannetier, Nicolas; Coquery, Nicolas; Moisan, Anaïck; Lemasson, Benjamin; Thomas, Sébastien; Grillon, Emmanuelle; Detante, Olivier; Rémy, Chantal; Payen, Jean-François; Barbier, Emmanuel Luc
A quantitative estimate of cerebral blood oxygen saturation is of critical importance in the investigation of cerebrovascular disease. While positron emission tomography can map in vivo the oxygen level in blood, it has limited availability and requires ionizing radiation. Magnetic resonance imaging (MRI) offers an alternative through the blood oxygen level-dependent contrast. Here, we describe an in vivo and non-invasive approach to map brain tissue oxygen saturation ( StO2 ) with high spatial resolution. StO2 obtained with MRI correlated well with results from blood gas analyses for various oxygen and hematocrit challenges. In a stroke model, the hypoxic areas delineated in vivo by MRI spatially matched those observed ex vivo by pimonidazole staining. In a model of diffuse traumatic brain injury, MRI was able to detect even a reduction in StO2 that was too small to be detected by histology. In a F98 glioma model, MRI was able to map oxygenation heterogeneity. Thus, the MRI technique may improve our understanding of the pathophysiology of several brain diseases involving impaired oxygenation.